Storage possibilities of scale insect predator Chilocorus bipustulatus (L.) eggs at different temperatures (Bollettino di zoologia agraria e bachicoltura, 2024)
Mass production and release of natural enemies are among applications related to biological control. Storage of the eggs and adults of natural enemies without depriving their characteristics is an important element for the support the release when needed in the intensive release period. In this study, possibilities have been investigated of the storage of 1, 3 and 5 day old eggs of Chilocorus bipustulatus (L.), one of the natural enemies of California Red Scale, Aonidiella aurantii (Maskell), kept at 4, 8 and 12°C for different periods. Effects of the storage at different temperatures and periods on hatching rate, rate of reaching adult stage and the sex ratio were examined.No hatching was observed on 1, 3 and 5 day old eggs of C. bipustulatus stored for 25 days at different temperatures except for one and 3 day old eggs stored at l2°C. The highest hatching rate (94%) was found with the 3 day old eggs kept for 5 days at 8°C. The highest rate of adult development was obtained with 5 day old eggs stored at 12°C for 5 days.The percentage of females reaching adult stage was higher than that of males.
Keywords: Chilocorus bipustulatus; eggs; storage; survival